THE PROBLEMS OF VOTE LOGISTICS AT THE 2019 SIMULTANEOUS ELECTIONS IN PRINGSEWU REGENCY - Asrianturi, Asrianturi; Kurniawan, Robi Cahyadi; Warganegara, Arizka (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2021)
Experience in the implementation of the Legislative Election and the Presidential/Vice-Presidential Election which were held simultaneously in 2019 raised various problems. One of the problems that arise was the problem of handling election logistics. The procurement of logistics equipment for general elections, especially ballots, was ideally carried out based on the principles of the right number, right type, right target, right time, right quality and efficiency. This paper aims to find out the problems of managing the logistics of ballots in the 2019 simultaneous elections that occurred in Pringsewu Regency and provide improvement efforts in the management of simultaneous election logistics. This study uses a qualitative descriptive analysis method by conducting a literature study and analyzing secondary data obtained regarding ballot logistics problems in the 2019 Simultaneous Election in Pringsewu Regency. The results of this study can be concluded that (1) the technical handling of ballot logistics in the 2019 simultaneous elections in Pringsewu Regency was more complicated than the staged elections. In practice, the logistics of ballots became more numerous and complex, resulting in several major problems. The main problems were delays in sending ballots, lack of ballots, damaged/ defective ballots being swapped between Electoral Districts. Furthermore, (2) the main problem of ballot logistics that occurred in the 2019 simultaneous elections in Pringsewu Regency could also be said to have also occurred in the previous 3 (three) elections, 2004, 2009 and 2014 which were a non-simultaneous electoral system or an electoral system that separated the implementation of the Legislative Election from the Presidential Election